Pengaruh Budaya Organisasi terhadap Kinerja Panitia Pemungutan Suara (PPS) Pilkada 2024 Sekecamatan Bajubang Kabupaten Batang Hari - Darma, Budi; Wulansari, Kasiyati Yunita; Fauziah, Fauziah; Kurnia, Raden Hebat (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the influence of organizational culture on the performance of the 2024 Regional Election Voting Committee (PPS) in Bajubang District, Batang Hari Regency. The population of this study was the entire Voting Committee (PPS) in Bajubang District, totaling 30 people. The data collection method for this research is through the use of questionnaires, interviews, and direct observation of the Bajubang District Voting Committee (PPS), then analyzed using a simple linear regression analyst. The research results prove that there is a positive and significant influence between organizational culture variables on the performance of the Voting Committee (PPS) in Bajubang District by 60%.